Resilience and Cultural Adaptation of the Kerinci Indigenous Community: Navigating Tradition in a Modernizing World - Mukhlis; Yetti, Hafiza; Despita, Wulan Famelya; Yetri, Amelia; Wardiman, Doki (Indigenous Southeast Asian and Ethnic Studies, 2025)
This study explores the resilience and adaptation strategies of the Kerinci Indigenous community in preserving their cultural heritage amidst modernization. Using a qualitative ethnographic approach, data were collected through participatory observations, in-depth interviews, and document analysis. Thirty key informants, including traditional leaders, community figures, and government representatives, were purposively selected. Thematic analysis revealed that the Kerinci community’s resilience is rooted in a strong social structure supported by religious principles (adat bersendi Syarak, Syarak bersendi Kitabullah) and cultural diversity, serving as essential social capital. The community balances tradition and modernity by strengthening cultural education, revitalizing traditional practices, fostering partnerships, utilizing local resources, and promoting environmental awareness. These strategies ensure the sustainability of their cultural heritage while adapting to technological and social changes. The findings offer valuable insights for Indigenous communities worldwide in navigating modernization while preserving their cultural identity. The Kerinci community demonstrates unique resilience by merging traditional and modern elements. They embrace technological innovations, traditional arts, and skill development, maintaining a balanced integration of old and new values. This structured resilience model highlights their ability to adapt without losing cultural authenticity. The study’s findings are expected to serve as a reference for broader Indigenous communities in developing preservation strategies and adaptation mechanisms. By doing so, the cultural heritage of the Kerinci Indigenous community, and others like it, can remain safeguarded, sustainable, and transmissible to future generations. This research underscores the importance of combining traditional values with modern approaches to ensure cultural sustainability in a rapidly changing world.